(untitled) (Eurasian Journal of Engineering and Technology, 2022)
The article considers the fact that there is a high probability of emergency situations on the basis of comparing seismically active zones and analyzing population density maps with a map of regions where reservoirs are located in Uzbekistan, increasing the population’s potential to reduce the consequences of the flood threat for the population living in areas around reservoirs and discussed issues of preliminary determination of the evacuation zone, determination of categories of displaced population, the number of tents, their placement, organization of a hygienic cycle in a tent city in order to maintain the life of the population.